2011
DOI: 10.1097/ta.0b013e318227adae
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Infections Associated With Combat-Related Thoracic and Abdominal Cavity Injuries

Abstract: Trauma-associated injuries of the thorax and abdomen account for the majority of combat trauma-associated deaths, and infectious complications are common in those who survive the initial injury. This review focuses on the initial surgical and medical management of torso injuries intended to diminish the occurrence of infection. The evidence for recommendations is drawn from published military and civilian data in case reports, clinical trials, meta-analyses, and previously published guidelines, in the interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 98 publications
0
17
0
Order By: Relevance
“…This has changed with the introduction of antibiotics and modern surgical management of wounds. This has resulted in the diminution of Gram-positive bacteria and emergence of more resistant ones particularly the aerobic and facultative anaerobic Gram-negative bacilli [3,7,8]. Our study in Libya showed that the infection rate among patients with war-associated infection was 42% with no variation according to the different regions where the injured patients came from.…”
Section: Wound Infectionsmentioning
confidence: 66%
“…This has changed with the introduction of antibiotics and modern surgical management of wounds. This has resulted in the diminution of Gram-positive bacteria and emergence of more resistant ones particularly the aerobic and facultative anaerobic Gram-negative bacilli [3,7,8]. Our study in Libya showed that the infection rate among patients with war-associated infection was 42% with no variation according to the different regions where the injured patients came from.…”
Section: Wound Infectionsmentioning
confidence: 66%
“…29 Postinjury infection following penetrating abdominal injury ranges from 4% to 31%. 29 Civilian and military literature has reported varying rates of infections after central nervous system injury, with a military study describing 408 patients with closed or penetrating head trauma evaluated and managed at Walter Reed Army Medical Center or National Naval Medical Center in Bethesda, MD. 30,31 There was a 9% rate of meningitis, with a rate of 26% in patients who had concomitant cerebrospinal fluid leakage from nose, ear, or wound.…”
Section: Traumatic Woundsmentioning
confidence: 99%
“…Intravenous metronidazole should be added if penetrating wounds of the abdomen or esophagus are suspected [29,30]. Intravenous metronidazole should be added if penetrating wounds of the abdomen or esophagus are suspected [29,30].…”
Section: Current Management Of Military Woundsmentioning
confidence: 99%